Professional handball coaches management of players' situated understanding during official games - Debanne, T.; Fontayne, P.; Bourbousson, J. (Psychology of Sport and Exercise, 2014)
Objectives: This study, based on the team cognition approach, investigated the information content expressed by coaches when helping players build or update their understanding of the unfolding game. The focus was on how this content fits into the usual task-work/teamwork and procedural/declarative taxonomies. Design: The data were collected through the audio and video recording of the communications and behaviors of three professional head coaches throughout a total of 15 games. We used deductive content analysis, crossing information contents related to task-work or teamwork with information contents related to declarative or procedural knowledge across the five game periods (first and second half of the first and second half-time, break-time period), and the three score differentials between the teams (favorable, balanced, and unfavorable). Method: We first performed a multivariate analysis of variance (MANOVA) using a 5 (Game Periods) × 3 (Score Difference) factorial design. Follow-up ANOVAs with repeated-measures were performed to identify the variables contributing to the multivariate effect. We then performed a repeated-measures analysis of variance for information contents related to declarative and procedural knowledge in occurrences of task-work and teamwork categories. Results: The results showed that the coaches expressed information related more often to players' procedural knowledge than to their declarative knowledge. We discovered two main effects (game periods and score differences) in coaches' information contents delivered to players. Information related to procedural knowledge was not addressed to the team as a whole, but to certain players. Conclusions: This suggests that an information flow was more distributed than shared.